Emerging roles of post‐translational modifications in signal transduction and angiogenesis. Issue 2 (8th October 2014) - Rahimi, Nader; Costello, Catherine E.; Pandey, Akhilesh; Moran, Michael F.
<x xml:space="preserve">Abstract</x> The vascular endothelial growth factor receptor‐2 (VEGFR‐2) belongs to the family of receptor tyrosine kinases and is a key player in vasculogenesis and pathological angiogenesis. An emerging picture of PTMs of VEGFR‐2 suggests that they play central roles in generating a highly dynamic and complex signaling system that regulates key angiogenic responses ranging from endothelial cell differentiation, proliferation, migration to permeability. Recent MS analysis of VEGFR‐2 uncovered previously unrecognized PTMs on VEGFR‐2 with a distinct function. The ligand binding extracellular domain of VEGFR‐2 is composed of seven immunoglobulin‐like domains highly decorated with N‐glycosylation, while its cytoplasmic domain is subject to multiple PTMs including Tyr, Ser/Thr phosphorylation, Arg and Lys methylation, acetylation and ubiquitination. Here we review the PTMs on VEGFR‐2, their importance in angiogenic signaling relays and possible novel therapeutic potentials.